Quality Management System Use of Foreign Language Apllications For Student Learning - Rainaldo Palandi; Angeline Pondaag; Putri Saron; Lheadis Tamuntuan; Dean Opuyu; Junior Wongkar (Jurnal Syntax Admiration, 2024)
The integration of quality management systems (QMS) into the use of foreign language applications has become increasingly relevant in enhancing student learning experiences. This study explores the effectiveness of foreign language learning applications, such as Duolingo and Babbel, when paired with QMS frameworks to monitor, evaluate, and improve learning outcomes. By adopting a systematic approach, the research examines how QMS principles—such as continuous improvement, performance measurement, and user feedback—can optimize the usability and pedagogical impact of these applications for students in diverse educational settings. Findings indicate that applying QMS to language applications fosters better alignment with educational objectives, improves user satisfaction, and enhances learning engagement. Key elements include regular tracking of learning progress, adaptive content customization, and structured feedback mechanisms. This approach also empowers educators to make data-driven decisions to support students' language acquisition effectively. The study concludes that incorporating QMS into the use of foreign language applications represents a viable strategy for advancing the quality of language education, promoting efficiency, and ensuring continuous improvement in student learning outcomes. Future research should explore the scalability of this approach across various disciplines and demographic groups to further validate its applicability.